2013
DOI: 10.1177/0261927x13504297
|View full text |Cite
|
Sign up to set email alerts
|

Actual and Potential Gender-Fair Language Use

Abstract: In two paper-and-pencil studies on university students and trainees, we studied how general language competence and the motivation to use accurate language are linked to people’s actual and potential gender-fair language use. Overall, participants’ actual gender-fair language use was lower than their potential. The higher the participants’ language competence, the higher their potential. Trainees’ actual gender-fair language use was predicted by the interaction of language competence and motivation to use accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Our findings are also consistent with the view that the current extensive use of the masculine only form (Blaubergs, 1980; Parks and Robertson, 1998; Bußmann and Hellinger, 2003; Mucchi-Faina, 2005; Koeser and Sczesny, 2014; Kuhn and Gabriel, 2014) may well-contribute to shaping, or at least maintaining, gender stereotypes. Consequently, enforcing or encouraging the use of pair forms in grammatical gender languages when referring to mixed gender groups or to groups whose gender composition is unknown or irrelevant seems to be an effective strategy to counter gender stereotypes.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are also consistent with the view that the current extensive use of the masculine only form (Blaubergs, 1980; Parks and Robertson, 1998; Bußmann and Hellinger, 2003; Mucchi-Faina, 2005; Koeser and Sczesny, 2014; Kuhn and Gabriel, 2014) may well-contribute to shaping, or at least maintaining, gender stereotypes. Consequently, enforcing or encouraging the use of pair forms in grammatical gender languages when referring to mixed gender groups or to groups whose gender composition is unknown or irrelevant seems to be an effective strategy to counter gender stereotypes.…”
Section: Discussionsupporting
confidence: 90%
“…For example, Sczesny, Moser, and Wood (2015) found in a fill-in-the-gap task that gender-balanced forms were used in only 40% of the gaps (Studies 1 and 2). Kuhn and Gabriel (2014) reported similar numbers, also using fill-in-the-gap tasks; in 66% (university students) or 60% (trainees) of their responses, participants used the masculine form only (GM) to refer to persons or groups of unknown gender.…”
Section: The Unsystematic Use Of Feminisation and Neutralisationmentioning
confidence: 82%
“…Language competencies may serve as a good initial candidate to explain the unsystematic use of feminisation and neutralisation, as overcoming traditional lexical forms may require both lexical and syntactic flexibility. Kuhn and Gabriel (2014), for example, showed that when explicitly asked to avoid GM terms, participants’ compliance depended on their level of production competence, as measured by the DaF (Jung, 1998), a standardised language test for German.…”
Section: The Unsystematic Use Of Feminisation and Neutralisationmentioning
confidence: 99%
“…Indeed, in the German-speaking part of Switzerland most women use feminine job titles to refer to themselves, though some women continue to use masculine forms (Schröter et al, 2012), indicating a variability in the gendered forms of professional titles used in reference to women. Importantly, gender-fair language rules were followed especially when speakers’ linguistic competence in German was high (Kuhn & Gabriel, 2014), suggesting that the use of gender-fair language forms signals linguistic competence. On the contrary, violating language standards signals linguistic incompetence, as has been shown in research on the devaluation of foreign language speakers (Giles & Coupland, 1991).…”
Section: Gender-fair Language Across Languages and Its Effectsmentioning
confidence: 99%